On the response of fiber reinforced elastomeric isolators (FREIs) under bidirectional shear loads. (December 2021) - Galano, Simone; Calabrese, Andrea; Losanno, Daniele
Abstract: Fiber Reinforced Elastomeric Isolators (FREIs) have been proposed as an alternative to Steel Reinforced Elastomeric Isolators (SREIs) and several studies have highlighted the advantages of this technology over conventional devices. When FREIs are unbonded to the top and bottom substructure, the bearings exhibit softening under imposed lateral deformations with or without instability depending on the aspect ratio of the device. Research studies available in literature have focused on the response of rectangular bearings when loaded in shear along their base. Very little is known on the lateral response of these devices under bidirectional shear loading. This study aims to assess the response of rectangular FREIs under combined axial and bidirectional shear loads and to show the effects of (i) the secondary shape factor of the bearing, of (ii) the axial pressure, of (iii) the horizontal loading direction on the stability of these devices. As result of a large set of analyses, stability domains have been derived which take into account all of the variables listed above. Based on the results of this work, simple to use design considerations can be derived. Results of this study contribute towards the real implementation of this technology particularly in developing regions of the world.